1997
DOI: 10.1038/sj.bjp.0701059
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of nitrovasodilators and cyclic GMP on ET‐1‐activated Ca2+‐permeable nonselective cation channel in rat aortic smooth muscle cells

Abstract: 1 In single vascular smooth muscle cells (VSMCs) isolated from the aortae of male Wistar rats, we examined the e ects of nitric oxide (NO) donors such as sodium nitroprusside (SNP) and S-nitroso-Nacetyl-DL-penicillamine (SNAP), and 8-bromo-guanosine-3':5'-cyclic monophosphate (8-bromo-cyclic GMP) on endothelin-1 (ET-1)-activated Ca 2+ -permeable nonselective cation channel by use of whole-cell recordings of patch-clamp technique and monitoring of intracellular free Ca 2+ concentration ([Ca 2+ ] i ) with fura-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…The activation of ERK1/2 depended on increased ROS levels, since antioxidants blocked ET-1-dependent ERK1/2 activation. ET-1 also increased [Ca 2ϩ ] i and ROS levels in AoSMCs, consistent with previous reports (21,31,41), but did not activate ERK1/2 or induce HIF-1␣ protein accumulation. The mechanism by which ROS leads to ERK1/2 activation in PASMCs is unclear, as is the reason why ET-1-induced increases in ROS do not activate ERK1/2 in AoSMCs.…”
Section: Discussionsupporting
confidence: 80%
“…The activation of ERK1/2 depended on increased ROS levels, since antioxidants blocked ET-1-dependent ERK1/2 activation. ET-1 also increased [Ca 2ϩ ] i and ROS levels in AoSMCs, consistent with previous reports (21,31,41), but did not activate ERK1/2 or induce HIF-1␣ protein accumulation. The mechanism by which ROS leads to ERK1/2 activation in PASMCs is unclear, as is the reason why ET-1-induced increases in ROS do not activate ERK1/2 in AoSMCs.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, concentrations above 10 −9 M lead to an increase in [(Ca 2+ ) i ] through the liberation of Ca 2+ from intracellular deposits, which induces a short and transient contraction phase, and also through the activation of VOCC, which induces a higher, sustained increase in [(Ca 2+ ) i ]. Thus, a contraction phase with a longer duration and higher magnitude is produced (Takuwa et al 1990;Komuro et al 1997;Minowa et al 1997;Zhang et al 1998). In contrast, lower ET-1 concentrations only induce the sustained phase; that is, the contraction in this case is mainly dependent on extracellular Ca 2+ Kawanabe et al 2002).…”
Section: +mentioning
confidence: 99%
“…Several researchers have shown that Ca 2+ -permeable nonselective cation channels (NSCC) are activated by stimulation of native ET A receptor in vascular smooth muscle cells (van Renterghem et al 1988;Chen and Wagoner 1991;Enoki et al 1995;Minowa et al 1997) and of recombinant human ET A receptors expressed in Ltk -cells (Enoki et al 1995). We have recently found that in A7r5 cells derived from rat thoracic aortic smooth muscle cells, ET-1 can activate three types of voltage-independent Ca 2+ entry channels: type-1 Ca 2+ -permeable NSCC (NSCC-1), type-2 Ca 2+ -permeable NSCC (NSCC-2) and store-operated Ca 2+ channel (SOCC), in addition to VOCC (Iwamuro et al 1998(Iwamuro et al , 1999.…”
Section: Introductionmentioning
confidence: 99%